2023
DOI: 10.2174/1573394719666230119142053
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy of Cancer: Quality and Prospective of Therapy based on Photosensitizer

Abstract: To kill cancer cells, photodynamic therapy (PDT) utilizes a light-sensitive medication and light. Light-sensitive drugs are absorbed by cancerous cells. The cells are then illuminated with a specific light or laser by a specialist and oxygen that destroys cancer cells is released. The present study aims to discuss the roles, advancements, and limitations of photodynamic therapy in cancer treatment. Photosensitizers and photosensitizing agents are used in photodynamic treatment to destroy cancer cells. Lasers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…19,20 However, limitations still remain, including insufficient endogenous H 2 O 2 in CDT and the dependence of PTT efficacy on the depth and location of tumor tissue. 21,22 Consequently, combination of these techniques or their integration with other modalities is gaining interest to optimize therapeutic outcomes and minimize side effects. 23−27 To achieve a synergistic effect, PDA is applied as a photothermal agent to enhance the Fenton catalytic activity, while copper or manganese ions serve as CDT agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 However, limitations still remain, including insufficient endogenous H 2 O 2 in CDT and the dependence of PTT efficacy on the depth and location of tumor tissue. 21,22 Consequently, combination of these techniques or their integration with other modalities is gaining interest to optimize therapeutic outcomes and minimize side effects. 23−27 To achieve a synergistic effect, PDA is applied as a photothermal agent to enhance the Fenton catalytic activity, while copper or manganese ions serve as CDT agents.…”
Section: Introductionmentioning
confidence: 99%
“…As precise and low-side-effect alternatives, photothermal therapy (PTT), chemodynamic therapy (CDT), targeted drug delivery, and immunotherapy have revolutionized breast cancer treatment. Recent clinical trials have demonstrated the enhanced efficacy of PTT and CDT in treating tumor cells. CDT effectively converts endogenous H 2 O 2 into lethal hydroxyl radicals (·OH) through Fenton or Fenton-like reactions. The primary metal catalysts used in CDT, namely iron, copper, and manganese, rely on H 2 O 2 in the tumor microenvironment without requiring external stimuli. Additionally, PTT uses the absorption of light energy to generate heat energy, eradicating cancer cells noninvasively. , To overcome challenges, such as limitations with photosensitizers and suboptimal H 2 O 2 levels in the tumor microenvironment, polydopamine (PDA) has shown promise as a biocompatible and NIR-induced photothermal conversion agent. , However, limitations still remain, including insufficient endogenous H 2 O 2 in CDT and the dependence of PTT efficacy on the depth and location of tumor tissue. , Consequently, combination of these techniques or their integration with other modalities is gaining interest to optimize therapeutic outcomes and minimize side effects. To achieve a synergistic effect, PDA is applied as a photothermal agent to enhance the Fenton catalytic activity, while copper or manganese ions serve as CDT agents. , Nevertheless, challenges remain, such as inadequate H 2 O 2 levels in the tumor microenvironment and inefficient targeting of composite nanoparticles. Some of the limitations of each method are overcome by exploiting the synergistic effect of CT, CDT, and PTT, which can enhance the tumor-killing efficiency and reduce the dosage to minimize the side effects.…”
Section: Introductionmentioning
confidence: 99%